Edward Stanly : Whiggery's tarheel "conqueror" - Brown, Norman D. (University of Alabama Press, 1974)
Raised under the "Ancient Standard of Federalism," Edward Stanly was a southern nationalist during a time of popular nullification and secession doctrines. Edward Stanly: Whiggery's Tarheel Conqueror is an unprecedented biography of Stanly's life, and recounts his fiery and controversial emergence in the Whig Party of North Carolina in the 1930s, his role as a champion of Whiggery in the United States House of Representatives 1837-1843 and 1849-1853, his candidacy for governor of California in 1857, his appointment by President Abraham Lincoln as a military governor of N
Keywords: Stanly, Edward, -- 1810-1872.; Stanly, Edward, -- 1810-1872; Legislators -- United States -- 19th century.; Parlementaires -- États-Unis -- 19e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY.; United States -- Politics -- Stanly, Edward -- Biographies; Biographies; Biographies.